ANALISIS PENGEMBANGAN OBJEK WISATA DANAU SEBEDANG MENJADI DESTINASI WISATA HALAL DESA SEMPALAI SEBEDANG, KECAMATAN SEBAWI KABUPATEN SAMBAS - Umi Ulfa; Nashirun; Radimin (Cross-Border Journal of Business Management, 2023)
ABSTRACT This research was conducted using qualitative methods with a descriptive approach. This type of research is categorized as field research. Data collection techniques through interviews, observation, and documentation. While the primary data source is tourism managers and traders or the local community of Lake Sebedang. Data analysis techniques use data collection, data reduction, and the final stage, namely drawing conclusions. The data validity techniques used are triangulation techniques and continuous observation techniques. The results of this study show that the current condition of Lake Sebedang has experienced a lot of development, one of the factors that support the development of Lake Sebedang, namely capital ranging from paved road access, cafes, culinary restaurants that can attract visitors to come to Lake Sebedang. The potential for the development of Lake Sebedang tourism objects to become halal tourist destinations is one of the potentials that have been developed such as natural tourism and culinary tourism, but Lake Sebedang still cannot be said to be halal tourism because it still does not meet the standards of the concept of halal tourism development such as there are still those who sell alcoholic beverages and lodging that is still free, there is no prohibition for women and men so that it is still in conflict with Islamic law.